2010
DOI: 10.1177/0743558410376828
|View full text |Cite
|
Sign up to set email alerts
|

Drug-Intake Methods and Social Identity: The Use of Marijuana in Blunts Among Southeast Asian Adolescents and Emerging Adults

Abstract: This article examines why Southeast Asian American adolescents and emerging adults in two urban settings prefer to use “blunts,” or hollowed-out cigars filled with marijuana, over other methods of drug intake. Rationales for preferring blunts were both instrumental and social. Blunts allowed users to more easily share marijuana, the preferred drug among their peers, and protected against potential adverse effects associated with the “high.” Blunts also allowed users to identify with the dominant style of drug … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 54 publications
0
28
0
Order By: Relevance
“…Blunt smoking tends to be over-represented among males, African-Americans, older youths, more recent birth cohorts, and urban residents (Golub et al, 2005; Timberlake, 2013). Prevalence has increased steadily over the past decade, and blunt use has become more widely diffused across racial/ethnic groups (Soller and Lee, 2010; Timberlake, 2013). Cigars used for blunts and ‘blunt wraps’ (i.e., cigar rolling papers) are widely available in tobacco shops, convenience stores, and liquor stores (Lipperman-Kreda et al, 2014; Sifaneck et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Blunt smoking tends to be over-represented among males, African-Americans, older youths, more recent birth cohorts, and urban residents (Golub et al, 2005; Timberlake, 2013). Prevalence has increased steadily over the past decade, and blunt use has become more widely diffused across racial/ethnic groups (Soller and Lee, 2010; Timberlake, 2013). Cigars used for blunts and ‘blunt wraps’ (i.e., cigar rolling papers) are widely available in tobacco shops, convenience stores, and liquor stores (Lipperman-Kreda et al, 2014; Sifaneck et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In that drug argot reflects shared values and beliefs, argot may indicate the boundaries between subcultures associated with different drugs. So, for example, the term “crackhead” when used by blunts smokers expresses their collective disdain for use of crack cocaine and its users (Furst et al, 1999; Soller & Lee, 2010) iv .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that Southeast Asian American youths in the East San Francisco Bay area participate in hip-hop subculture, but that their participation is nuanced by specific aspects of their unique social status as second-generation Asian Americans and children of refugees as well as by their relationships to other youths in their neighborhoods (Lee & Kirkpatrick, 2005; Soller & Lee, 2010). Use of Ecstasy by Bay Area Southeast Asian youths may be an expression of their identification with and participation in a local youth cultural form known as “hyphy.” Hyphy is a subgenre of hip-hop music that was developed in the Bay Area in the 1990s by recording artists including E40 and the late Mac Dre (Lee et al, 2011).…”
Section: Youth Drug Use and Local Knowledgementioning
confidence: 99%
See 1 more Smart Citation
“…These partners had worked together in various configurations for ten years prior to the project, including federally-funded research and intervention projects on the etiology of problematic substance use among U.S. Southeast Asians (1517), and had a mutual interest in improving the health of Cambodian Americans through research and community engagement. Following these projects we conducted focus groups with key community leaders to assess unmet community behavioral health needs and consider new approaches to address these needs.…”
Section: Objectivesmentioning
confidence: 99%